Desenvolvimento e fitossanidade de ameixeiras tratadas com silício em sistema orgânico - Ferreira, Silvana Girotto Martins (2012)
The aim of this study was evaluate the effect of foliar silicon applied in grapevine cv. Syrah for control of downy mildew (Plasmopara viticola) and plum cv. Plume 7 in the control of bacterial (Xanthomonas arborícola pv. pruni), oriental fruit moth (Grapholita molesta), and greenbug (Myzus persicae) as well as in the plants development. For all experiments was used a commercial product called AgriSil® (98% SiO2). In December 2010 was tested the germination spores of P.viticola in the Phytopathology laboratory of CEDETEG. Field experiments were conducted at the experimental orchard of Agronomy Department of Unicentro for two consecutive cycles (2010/2011 and 2011/2012), which were evaluated the increasing concentrations of Si. In the first cycle the treatments were 0, 1, 2, 4 and 8 g L?¹ of Si, both to grapevine as for plum. The applications were interspersed with fortnightly sprays of products used in the organic system (Bordeaux mixture, neem extract, cinnamon extract, vegetable oil). In the second cycle evaluations for the plum were kept the same procedures as the first cycle. However, for the vine were suspended spraying with products of organic, ..... and doses were used 0, 2, 4, 8 or 16 g L?¹ SiO2. In the second cycle evaluations for the plum were kept the same procedures as the first cycle. However, for the vine were suspended spraying with products of organic and doses were used 0, 2, 4, 8 or 16 g L?¹ SiO2. The severity of disease in vine leaves was determined by visual evaluations by diagrammatic scale, and subsequent determination of the area under the curve progression of the disease (AUDPC). The length and diameter of the branches of the vine and plum were measured at two-year experiment to evaluate plant development. At the end of the second year was determined, dry matter (DM) of shoots and roots of the vine and the Si content of grapevine leaf and plum. To evaluate the severity of bacteriosis two assessments were made every two weeks by collecting 10 leaves per plant using diagrammatic The oriental fruit moth attack was evaluated by doing the percentage of pointers attacked and the aphid infestation was made by counting individuals in the fields that were marked. For the development of plants was measured the length and the diameter of the branches marked. To test the germination of P. viticola the quadratic effect was observed as a function of concentrations of SiO2 (0, 1, 2, 4 or 8 g L?¹) at 12 and 24 hours after the onset of incubation the sporangia. In the field, the two assessment cycles, did not affect the control of downy mildew by the application of Si. In the same way, the length and the diameter of shoots did not show significant results. For MS cubic effect was observed in both treatments with Bordeaux mixture used in the shoot and in the roots, especially the dose 2 g L?¹ of Si with the highest MS and Bordeaux mixture when no effect was found for both linear shoot as to the roots. For the plum bacteriosis, a reduction of the disease for all doses was used, with quadratic regression analysis. It was found that the progress of disease in plants where silicon was applied at a concentration of 1 g L1 was 48% lower than in the control, whereas treatment with 2, 4 and 8 g L?¹ silicon reduced, respectively , 71.5%, 72.1% and 79.5% compared to the control. For the attack of oriental fruit moth and aphids, as well as to the growth and development of plants plum Si showed no significant difference between the doses used. The results of the analyzes of leaf Si for both the vine for as plum, showed a linear regression analysis